Improving ethanol tolerance of Escherichia coli by rewiring Its global regulator cAMP receptor protein (CRP) - Chong, Huiqing (2013)
A major challenge in bioethanol fermentation is the low tolerance of the microbial host towards the end product bioethanol. Here we report to improve the ethanol tolerance of E. coli from the transcriptional level by engineering its global transcription factor cAMP receptor protein (CRP), which is known to regulate over 400 genes in E. coli. Three ethanol tolerant CRP mutants (E1– E3) were identified from error-prone PCR libraries. The best ethanol-tolerant strain E2 (M59T) had the growth rate of 0.08 h^-1 in 62 g/L ethanol, higher than that of the control at 0.06 h^-1. The M59T mutation was then integrated into the genome to create variant iE2. When exposed to 150 g/l ethanol, the survival of iE2 after 15 min was about 12%, while that of BW25113 was ,0.01%. Quantitative real-time reverse transcription PCR analysis (RT-PCR) on 444 CRP-regulated genes using OpenArrayH technology revealed that 203 genes were differentially expressed in iE2 in the absence of ethanol, whereas 92 displayed differential expression when facing ethanol stress. These genes belong to various functional groups, including central intermediary metabolism (aceE, acnA, sdhD, sucA), iron ion transport (entH, entD, fecA, fecB), and general stress response (osmY, rpoS). Six up-regulated and twelve down-regulated common genes were found in both iE2 and E2 under ethanol stress, whereas over one hundred common genes showed differential expression in the absence of ethanol. Based on the RT-PCR results, entA, marA or bhsA was knocked out in iE2 and the resulting strains became more sensitive towards ethanol.